Sulphide pollutants elimination and degradation in petroleum wastewater by ozonation process - Kadhim, Wafaa A.; Al-Jadir, Thaer; Albrazanjy, Mohammed G.; Al-Rubaiey, Njim A; Dakhil, Ali Mohammed; Al-Saedi, Noor Dheyaa; Mohd Hairul, Ab. Rahim (IOP Publishing Ltd, 2021)
An efficient and robust chemical oxidation process using an OZ-3G ozone generator was developed and investigated to degrade and reduce sulphide toxicity in petrochemical wastewater. Different concentrations of sulphide in synthetic wastewater were prepared and evaluated using the Spectrophotometric technique. The values of Chemical Oxygen Demand (COD) and pH were also studied. The obtained results demonstrated that 100 minutes of ozone treatment removed 97.4 % for 40 mg/L concentration. The pH was decreased gradually with the increase along the time of oxidation. Based on the ozone method's significant results, ozonation can be considered a potential candidate method for wastewater treatment in petroleum refineries.